The Youth Olympic Games - Some ethical issues - Parry, J. (Sport, Ethics and Philosophy, 2012)
This paper presents some of the background to the development of the Youth Olympic Games, the principles underlying them, and some of the practical challenges in implementing them. Regarding the sports programme, modifications from the Olympic Games programme are noted, and innovations examined in terms of underlying values, such as immaturity and harm, talent identification and early specialisation, and the exploitation of young athletes. Issues arising from the first edition of the YOG include participation and equality of opportunity, selection of sports and nations for the programme, age and fairness, age falsification and cheating, victory and defeat, participation and excellence, and political discrimination, peace and international understanding. The paper concludes that, although many of the above issues present already-existing challenges for the Olympic movement, albeit in a novel form, there were also some novel issues thrown up by a `youth` edition of the Olympic Games, and many of the ethical and other value questions raised have much wider applications and consequences. It is to be hoped that ethical issues arising out of the YOG will provide a fresh impetus towards discussions as to the nature and promotion of ethical sport.